Knowing how to teach well : teachers reflect on their classroom practice - Batten, Margaret; Marland, Perc.; Khamis, Mon. (Hawthorn, Vic. : Australian Council for Educational Research, 1993)
The context of the project. Students' perceptions of effective teaching. Exploration of teachers' professional craft knowledge: the Victorian study. Exploration of teachers' professional craft knowledge: the Queensland study...
Keywords: Education; Australia; Teaching; Teachers; Teaching -- Evaluation -- Australia; Teachers -- Rating of -- Australia